PENINGKATAN KEAKTIFAN DAN PRESTASI BELAJAR MATEMATIKA DENGAN TALKING STICK PADA SISWA KELAS VII F SMP N 2 SRANDAKAN - Retno Wulansari; Agustina Sri Purnami (Universitas Sarjanawiyata Tamansiswa, 2015)
The purpose the research to improve the activity and achievement of learning mathematics with the Talking Stick method in class VII F SMP N 2 Srandakan. The type of this research is a classroom action research. The subject of the research are the students grade VII F SMP N 2 Srandakan it consists of 24 students. The object of this research is activity and achievement of learning mathematics with the Talking Stick method. The result of the study shows that after this learning model, students’ activity and achievement has an increase. Students’ activity has increase in pre cycle from 56,25% become 64,93% and an increase in cycle II become 72,92%. Beside that the subjection average of students achievement has an increase in pre cycle shows 53,43 with Minimum Completenes Criteria ‘KKM’ is 12,5% consists of 3 students. In cycle I has an increase become 66,94 with KKM is 41,67% consist of 10 students where as in cycle II shows the increasa become 82,54 with KKM is 75% consist of 18 students. In pre cycle to cycle I there are 2 students whose value is fixed and the 22 students has increased. Then in cycle I to cycle II there are 1 student whose value is fixed and the 23 students has increased.